Professional Education and Practice: Ottawa Police Service Officer and Educator Perceptions of Use of Force Education and Experiences - Jubril, Annette (Université d'Ottawa / University of Ottawa, 2022)
In the last 20 years, the number of incidents involving police use of force (UOF) has nearly doubled in Canada (Marcoux & Nicholson, 2018). There have been at least 460 documented fatal police encounters across Canada between the years 2000 and 2017 and at least 1,860 police UOF investigations specifically in Ontario (Dunn, 2018; Ontario Human Rights Commission, 2018). According to a 2019 annual report by Ottawa Police Service (OPS, 2019), a municipal police service in Ontario, between the years 2018 and 2019, OPS reported a 21% decrease (from 767 to 607) of applications of force among officers and a 15% increase (from 529 to 609) of UOF reports. Although the latter data is relevant to Ottawa, to better understand and potentially minimize negative police-civilian encounters, both specifically and on a larger scale, this Canadian-focused study centers on policing as well as the context at OPS and explores the extent to which professional education (PE) influences professional practice (PP). It does so by reviewing OPS’s UOF training and gathering perspectives from patrol officers and UOF educators. Using a qualitative instrumental case study (QICS) research design, the study analyzes the UOF training materials that OPS used to certify and recertify officers between the years 2010 and 2021. It also incorporates semi-structured interviews with officers and educators to gather insights on how participants define UOF, their perspectives on their pre-service and in-service training, as well as how they relate their PE to their police-civilian encounters, particularly when they used or did not use force. A document analysis of the data revealed that OPS’s UOF training uses both traditional as well as progressive and collaborative approaches to educate and relate to officers. Such approaches also aim to promote appropriate communication and de-escalation skills. At the same time, the learning objectives found in the lesson plans lack the detail needed to signify that officers have achieved the intended goal of the training. Among the important themes that emerged from the interviews were 1) the differences in priorities, between the officers and educators, concerning UOF training, 2) the value that officers place on their instructors’ experiences, 3) the challenges that educators face while adhering to provincial expectations, and 4) the integral role that training and life experiences play during police-civilian encounters. The relevance of social media was another significant theme that emerged within the study, particularly considering the participants’ views on the current social climate of policing (i.e., how the public perceives the police as well as the contentious debate about defunding the police). With limited research on police perspectives and issues specific to policing in Canada, the present study, by virtue of access to OPS’s training materials, patrol officers and UOF instructors, seeks to initiate rich and meaningful discussions about PE and PP. It also aims to encourage reflection among educators, policy-makers and society so as to address and deepen our understanding of issues related to education.
Keywords: professional education and practice; police use of force and training; police officer and educator perceptions; qualitative instrumental case study; document analysis; (reflexive) thematic analysis; Ottawa, Ontario, Canada